CORPORATE INTERNAL COMMUNICATION: IMPLEMENTATION IN THE HUMAN RESOURCES AND GENERAL AFFAIR DIVISION - Punkie Paramita Dewi; Sushanty Chandra Dewi; Kania Farida; Retno Widowati (ASIAN PUBLISHER, 2022)
The communication process plays a vital role in a company. The company’s goal will not be reached if there is no proper communication inside. Therefore, this study aims to interpret the internal communication activity inside a company, especially within Human Capital and General Services. Those departments were chosen because the activities inside play a significant role related to the service for all employees. A descriptive qualitative method was used to analyze the objects. Through the method, it was found that certain barriers still happened during daily work. Either inside each department or cross-departments. To clear the barriers, researchers deliver suggestions consists of three points, which are vertical. horizontal, and diagonal. Those points are explained as giving a clear brief and instruction, keeping a proper communication, and organize a regular meeting with th related department.